Cultural Distance and Foreign Drama Enjoyment: Perceived Novelty and Identification with Characters. Issue 3 (2nd July 2016) - Baek, Young Min; Kim, Hye Min
Abstract : This study employs a cross-cultural perspective to examine how local audiences perceive and enjoy foreign dramas and how this psychological process differs depending on the cultural distance between the media and the viewing audience. Using a convenience sample of young Korean college students, this study, as predicted by cultural discount theory, shows that cultural distance decreases Korean audiences' perceived identification with dramatic characters, which erodes their enjoyment of foreign dramas. Unlike cultural discount theory, however, cultural distance arouses Korean audiences' perception of novelty, which heightens their enjoyment of foreign dramas. This study discusses the theoretical and practical implications of these findings, as well as their potential limitations.